(untitled) (LACCEI, 2024)
In the city of Cajamarca, there has been a high demand for welding services on metal parts and production of automotive spare parts. To address this shortage, a diagnosis was carried out to establish the problem and prioritize its solution. With the aim of improving the assembly automation system for trailers, it was decided to automate the rolling operation in order to guarantee the quality and finish of the sheet that will later be used in the assembly of the trailers. The electronic software Cade_Simu was used to create electrical control diagrams, and PLCs were implemented to achieve a more efficient count of the trailers produced by the machines, as well as better control of the production of rolled sheets. In addition, the SCADA system was integrated to allow for acquisition, supervision and control of the trailer design.